Aktivitas Antibakteri dan Antioksidan Daun Pecut Kuda (Stachytarpheta jamaicensis L.) Secara Invitro - Kumala, Shirly; Bekti, Novi Dyah Purnama (Indonesian Research Gateway)
Pecut Kuda leave (Stachytarpheta jamaicensis L.) was one of the many medicinal plants found in Indonesia and it has been widely used by the people in Indonesian to cure infection of tractus urinarius, pharingitis, hepatitis. Although, it has been very popular traditional medicine, very little scientific data were collected until now. This study focused on preliminary studies of antibacterial and antioxidant activity of Pecut Kuda leaves. Extracts were obtained using n-hexane, ethyl acetate and methanol. The antibacterial activity test was performed using the agar diffusion method against Staphylococcus aureus and Escherichia coli. While antioxidant activity was performed by the colorimetric method using DPPH radical reduction. The results showed that n-hexane extracts did not have either antibacterial or antioxidant activity. The ethyl acetate extract had zone inhibition (DDH) between 7 to 11.67 mm against S. aureus bacteria, whereas against E. coli with DDH between 7.67 to 10.83 mm, and had IC50 value of 182.97%. The methanol extract had DDH between 8.33 to 13.67 mm against S.aureus, whereas against E. coli bacteria with DDH between 9 to 14.67 mm, and IC50 value of 14.28%. In conclusion, ethyl acetate and methanol extract of Pecut kuda leaves have antioxidant and antibacterial activity against S. aureus and E. coli bacteria.